Suing the Oligarchy of Ownership and Control of Agricultural Land in Indonesia: A Maqashid Sharia Review of the Land of Agrarian Reform Objects (TORA) Exceeding the Maximum Boundary - Herlindah Herlindah; Moh Anas Kholish; Andi Muhammad Galib (Sharia and Law Faculty, 2022)
This article aims to identify and analyze Land Objects of Agrarian Reform (TORA) on agricultural land that exceeds the maximum limit in positive law in Indonesia, as well as analyze maqashid sharia and the future of TORA as a legal standing for lawsuits against the oligarchs of control and ownership of agricultural land in Indonesia. This article is a normative legal research with statutory and conceptual approaches. The results of this study indicate that in positive law in Indonesia there are six characteristics of TORA Agricultural land exceeding the maximum limit, namely: (1) The subject of the original owner's rights is an individual with the size of one family; (2) agricultural land is divided into two types, namely paddy fields and dry land; (3) non-HGU land tenure, temporary and limited rights obtained from the government and legal entities; (4) there is a violation of the maximum land area; (5) TORA exceeds the maximum limit of transfer to the state based on forced expropriation; (6) TORA in excess of the maximum limit is given to the subject of land recipient rights based on a government stipulation. In addition, the results of this study also show that the rules regarding land as objects of agrarian reform as stipulated in positive law in Indonesia are very compatible with the spirit of maqashid sharia, namely hifz al-mal. In the perspective of contemporary maqashid sharia, hifz al-mal is not only interpreted as a prevention of monopoly and exploitation of wealth by oligarchic elites, but also must be developed philosophically regarding the distribution of resources for society. If linked in this article, hifz al-mal which is one of the pillars of maqashid sharia must also be developed in the context of making positive rules regarding the distribution of ownership and control of land in a fair and equitable manner. Artikel ini bertujuan untuk mengidentifikasi dan menganalisis Tanah Objek Reforma Agraria (TORA) pada tanah pertanian kelebihan batas maksimum dalam hukum positif di Indonesia, serta menganalisis maqashid syariah dan masa depan TORA sebagai legal standing atas gugatan terhadap oligarki penguasaan dan kepemilikan tanah pertanian di Indonesia. Artikel ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Adapun hasil dari studi ini menunjukkan bahwa dalam hukum positif di Indonesia terdapat enam karakteristik TORA Tanah pertanian kelebihan batas maksimum yaitu: (1) Subjek hak pemilik asal adalah orang perorangan dengan ukuran satu keluarga; (2) tanah pertanian dibedakan menjadi dua jenis yaitu tanah sawah dan dan tanah kering; (3) penguasaan tanah bukan HGU, hak-hak sementara dan terbatas yang didapat dari pemerintah dan badan-badan hukum; (4) terjadi pelanggaran luas batas maksimum tanah; (5) TORA kelebihan batas maksimum beralih kepada negara berdasarkan pengambilalihan secara paksa; (6) TORA kelebihan batas maksimum diberikan kepada subjek hak penerima tanah berdasarkan penetapan pemerintah. Selain itu, hasil studi ini juga menunjukkan bahwa aturan-aturan tentang tanah objek reforma agraria sebagaimana ketentuan dalam hukum positif di Indonesia sangat kompatibel dengan spirit maqashid syariah yaitu hifz al-mal. Dalam perspektif maqashid syariah kontemporer, hifz al-mal bukan hanya dimaknai sebagai pencegahan atas monopoli dan eksploitasi harta dari para elit oligarki, namun juga harus dikembangkan secara filosofis tentang distribusi sumber daya bagi masyarakat. Jika dikaitkan dalam artikel ini, maka hifz al-mal yang menjadi salah satu pilar maqashid syariah juga harus dikembangkan dalam konteks pembuatan aturan secara positif tentang distribusi kepemilikan dan penguasaan tanah secara adil dan merata.